DEVELOPING 21ST-CENTURY SKILLS AMONG STUDENTS THROUGH DIGITAL TECHNOLOGIES IN BIOLOGY LESSONS - Suyunova Guljakhon Uchkunovna; Gafforova Sevara Akbarali qizi; Ergasheva Rukhshona Khusan qizi (Modern American Journals, 2025)
This article analyzes the methodology of developing 21st-century skills among students in biology lessons through digital technologies. The study examines methods and practices aimed at fostering critical thinking, creativity, teamwork, and effective use of technology among students with the help of digital tools. Experimental results show that interactive programs, mobile applications, and online resources can effectively enhance students’ learning processes in biology. The article highlights the importance of digital technologies in pedagogical practice and their role in the education system.
Keywords: Biology, Digital technologies, Interactive programs, Online platforms, Critical thinking, Creativity, Teaching methodology, Educational technologies.